Contents Practicality of the Popular Ethnobotany Scientific Book of Gliricidia maculata in the Tamiang Hill Forest Area, Tanah Laut Regency - Naufal Hafidh Mahdi Sujarwo Putra; Dharmono Dharmono; Mahrudin Mahrudin (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
The teaching materials need to see the reader's ability for how to understand the intent, to know the feasibility, and also for improvement practical content. This study wants to describe the contents practicality of popular scientific book on the ethnobotany’s Gliricidia maculata as supporting material for ethnobotany courses in biology education, FKIP ULM Banjarmasin. Ethnobotany popular scientific book refers to Tessmer Formative Evaluation with the steps on content practicality using individual tests (one to one) and also the content practicality assessment instrument too. The research subjects were 3 students of Biology Education FKIP ULM Banjarmasin who had passed the ethnobotany course and for the average result has 3.6 with very good criteria. Teaching materials that accordance with student characteristics allow more contextual learning experience, complete learning experience, developed according to the student conditions and implementation based on indicator as guidance.Abstrak Bahan ajar yang dikembangkan perlu melihat kemampuan pembaca dalam memahami maksud yang ingin disampaikan, mengetahui keterlaksanaan dan kemudahan penggunaan bahan ajar untuk penyempurnaan melalui suatu kepraktisan isi. Penelitian ini bertujuan untuk mendeskripsikan kepraktisan isi buku ilmiah populer etnobotani tumbuhan Gliricidia maculata sebagai materi penunjang mata kuliah etnobotani di pendidikan biologi FKIP ULM Banjarmasin. Buku ilmiah populer etnobotani sebagai bahan ajar dikembangkan melalui Evaluasi Formatif Tessmer dengan tahap yang dilakukan pada kepraktisan isi menggunakan uji perorangan (one to one) serta instrumen penilaian kepraktisan isi juga mengacu pada Tessmer. Subjek penelitian merupakan 3 orang mahasiswa Pendidikan Biologi FKIP ULM Banjarmasin yang dinyatakan telah lulus mata kuliah etnobotani. Hasil rata-rata kepraktisan isi buku ilmiah populer memiliki nilai 3,6 dengan kriteria sangat baik. Bahan ajar yang sesuai dengan kondisi mahasiswa dapat membuat pengalaman belajar yang semakin kontekstual, pengalaman belajar yang utuh, serta dikembangkan sesuai kebutuhan mahasiswa dan keterlaksanaan ditentukan berdasarkan indikator yang dijadikan pedoman.